2016
DOI: 10.12972/kjhst.20160071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phytochemicals, Quality Attributes,and Antioxidant Activities in Commercial Tomato Cultivars

Shiva Ram Bhandari,
Young Chae,
Jun Gu Lee

Abstract: To assess South Korean commercial tomato cultivars, regular and cherry tomato cultivars were grown in the greenhouse and evaluated for color attributes, titratable acidity, pH, total soluble solids, carotenoids (lycopene and β-carotene), total phenols, flavonoids, vitamin C, and antioxidant activity. Significant differences (p < 0.05 using Duncan's multiple range test (DMRT)) were observed in the levels of most phytochemicals, quality parameters, and antioxidant activity among the twenty South Korean tomato cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In year 2, the total sugar was 24% lower than that in year 1, and the reducing sugar was 25% higher than that in year 1 (Figure 3E and F). The present variety of cherry tomato had a lower SSC/TTA than cultivars of commercial cherry tomato; therefore, this variety of cherry tomatoes is less sweet than the commercial cultivars (Bhandari, Chae, & Lee, 2016). Pre-harvest factors such as soil properties, nutrition, temperature, irrigation, genetics and fruit maturity may influence fruit quality (Dorais, Ehret, & Papadopoulos, 2008;Luna, Selma, Tudela, & Gil, 2013).…”
Section: Resultsmentioning
confidence: 81%
“…In year 2, the total sugar was 24% lower than that in year 1, and the reducing sugar was 25% higher than that in year 1 (Figure 3E and F). The present variety of cherry tomato had a lower SSC/TTA than cultivars of commercial cherry tomato; therefore, this variety of cherry tomatoes is less sweet than the commercial cultivars (Bhandari, Chae, & Lee, 2016). Pre-harvest factors such as soil properties, nutrition, temperature, irrigation, genetics and fruit maturity may influence fruit quality (Dorais, Ehret, & Papadopoulos, 2008;Luna, Selma, Tudela, & Gil, 2013).…”
Section: Resultsmentioning
confidence: 81%
“…Phenolic compounds are important secondary metabolites in plants that function as natural antioxidants and prevent chronic diseases related to excess free radicals by reducing oxidative stress [40,41]. Total phenolics correspond to the mean response of all major phenolic compounds present in fruits and vegetables [42]. Previous reports have shown In the present study, significant differences (p < 0.05) between maturity stages and elicitors treatment were also observed in β-carotene content and showed the same trend as lycopene (Figure 2B).…”
Section: Effect Of Preharvest Meja and Sa Treatments On Total Phenoli...mentioning
confidence: 99%
“…Phenolic compounds are important secondary metabolites in plants that function as natural antioxidants and prevent chronic diseases related to excess free radicals by reducing oxidative stress [40,41]. Total phenolics correspond to the mean response of all major phenolic compounds present in fruits and vegetables [42]. Previous reports have shown that quality of fruits and vegetables could be improved by elicitors treatments by inducing accumulation of total phenolics in artichoke [43], pack choi [11] and lemon fruit [30], as a result of enhanced phenylalanine ammonia lyase (PAL) activity and reduced activity of polyphenol oxidase (PPO) [44].…”
Section: Effect Of Preharvest Meja and Sa Treatments On Total Phenoli...mentioning
confidence: 99%
See 1 more Smart Citation
“…Decayed fruits Fruit decay %= 100 Total number of fruits × Phytochemical screening: Form each crude extract stock solution was prepared. The stock solution was then subjected to different tests for analysis of phytochemicals by using the standard procedures as mentioned by described by Bhandari et al [25].…”
Section: Titratable Aciditymentioning
confidence: 99%